Perceived Effects of COVID-19 Pandemic on Food Security in Southeast Nigeria - Munonye, Jane; Osuji, Emeka; Olaolu, Michael; Okoisu, Anthony; Obi, Joy; Eze, Gladys; Ibrahim-Olesin, Sikiru; Njoku, Loveday; Amadi, Mark; Izuogu, Chibuzo; Azuamairo, Gillian (Frontiers in Sustainable Food Systems, 2022)
The present study evaluated the perceived effects of the COVID-19 Pandemic on food security in Southeast Nigeria. A multi-stage random technique was used to select 209 households. Data for the study were collected with the aid of a structured questionnaire and were analyzed using descriptive statistics, z-test, food security model, and Tobit regression model. Results showed that the mean household size was 9.6 persons, which indicates a large household size. The percentage rate of food consumption of the households before the Pandemic was higher relative to the COVID-19 event. Again, exorbitant prices of food materials were noticed during the COVID-19 as compared to the period before the Pandemic. About 10.5% of the households met the minimum food requirements as proposed by World Health Organization (WHO), and Food and Agriculture Organization (FAO) as against the majority of 76.1%. The three dimensions of food security which include availability, accessibility, and utilization were interposed by a number of factors, such as artificial scarcity, and an increase in food prices. Furthermore, social distancing and lockdown imposition were COVID-19 determinants of the food security status of households in the Southeast Nigeria. About 24% of the households were food-secured compared to 76% that were insecured during the Pandemic. Robust and effective food and agricultural policy formulations and implementations were recommended in Southeast Nigeria.